Persuasive Rhetoric in Health Tourism Websites: Effective Verbal Strategies for Customer Engagement - Ganna Zakharova Garcia (Journal of Vasyl Stefanyk Precarpathian National University)
In the competitive field of tourism marketing, verbal strategies play a crucial role in promoting products and services, particularly in specialized areas like health tourism. To effectively engage and persuade potential tourists, marketers employ specific linguistic techniques that shape positive impressions, guide perceptions, and ultimately influence decision-making processes. The choice of verbal content in such contexts is essential, as it directly impacts the persuasiveness of the promotional materials. While tourism marketing shares similarities with broader digital marketing practices, it also exhibits distinct characteristics tailored to the unique demands of promoting travel experiences. This article provides an examination of the verbal strategies employed by prominent health tourism websites, focusing specifically on the “Karpaty” resort and “Solva Resort & SPA” in Ukraine. By analyzing the linguistic features used to promote health tourism services, the study sheds light on how language is strategically used to attract and persuade potential visitors. The analysis delves into the ways in which certain verbal elements are utilized as persuasive tools to encourage users to engage with the websites and make purchasing decisions. The results of this study present concrete examples from the resorts' websites, demonstrating the practical application of some verbal strategies in a real-world context. These findings reveal how persuasive language, tailored specifically for health tourism, can significantly enhance the appeal of services and lead to increased consumer engagement. This article contributes to a deeper understanding of how verbal content can be crafted to optimize persuasion in a highly competitive market. The novelty of this research lies in its focus on the intersection of language and health tourism, an area that has received limited attention in previous studies.